The Routledge International Handbook of European Social Transformations - Vihalemm, Peeter; Masso, Anu; Opermann, Signe (Taylor & Francis, 2022)
This book focuses on social transformations as one of the central topics in the social sciences. The study of European social transformations is very valuable in the context of universal discussions within social sciences: explaining invariable, universal attributes of societies and examining changing attributes. The book consists of 20 chapters on European social transformations, written from the perspectives of distinguished scholars from such disciplines as economics, political science, educational science, geography, media and communication studies, public management and administration, social psychology and sociology. The temporal and spatial range of the book is wide, including such global changes as time-space compression, focusing particularly on change processes in Europe during the last two decades. The book consists of four main parts, beginning with an overview of the theoretical and methodological approaches, and then focusing separately on post-communist transformations, institutional drivers of social transformations in the European Union, and European transformations in the context of global processes. The book presents current theoretical, empirical and methodological approaches that complement the scientific literature on social transformations. This book is both an invaluable resource for scholars and an indispensable teaching tool for use in the classroom and will be of interest to students, academics, and policy-makers studying how this diverse region has changed over recent years.